PENGARUH GROWTH OPPORTUNITY, FIRM SIZE, DAN LIQUIDITY TERHADAP KEPUTUSAN HEDGING PADA PERUSAHAAN PERBAN KAN INDONESIA - SARAGIH, FRISKA (Jurnal Ilmu Manajemen (JIM), 2017)
Hedging is one of the alternatives used to minimize risk in the company, especially the risk due to exchange rate fluctuations. The banking company is the company that has the highest capital sourced from the debt, banking operational activities are also very close to foreign exchange. So it is possible to conduct hedging activities to protect the company from the risk of exchange rate fluctuations. The purpose of this study was to determine the effect of growth opportunity, firm size, and liquidity of the hedging decision on Indonesian banking company. In this study, measurement companies use hedging or not will be seen in the annual financial statements. The object used in this study were banking companies listed in Indonesia Stock Exchange for the period 2012-2015. Sample in this study uses 28 banks by using purposive sampling method. This study uses a quantitative approach and data used secondary data. The analytical method used is logistic regression. The results showed that the variable growth opportunity and firm size have a significant positive effect on hedging decision making. The liquidity variable did not influence hedging decision in Indonesian banking company. This study shows that the higher the value of growth opportunity and firm size will increase the probability of using hedging activity in banking companies in Indonesia. Key word: hedging, growth opportunity, firm size, leverage.